Arbuscular mycorrhizal fungal and soil microbial communities in African Dark Earths - Camenzind, Tessa; Hammer, Edith C; Lehmann, Johannes; Solomon, Dawit; Horn, Sebastian; Rillig, Matthias C; Hempel, Stefan (Oxford University Press, 2018)
The socio-economic values of fertile and carbon-rich Dark Earth soils are well described from the Amazon region. Very recently, Dark Earth soils were also identified in tropical West Africa, with comparable beneficial soil properties and plant growth-promoting effects. The impact of this management technique on soil microbial communities, however, is less well understood, especially with respect to the ecologically relevant group of arbuscular mycorrhizal (AM) fungi. Thus, we tested the hypotheses that (1) improved soil quality in African Dark Earth (AfDE) will increase soil microbial biomass and shift community composition and (2) concurrently increased nutrient availability will negatively affect AM fungal communities. Microbial communities were distinct in AfDE in comparison to adjacent sites, with an increased fungal:bacterial ratio of 71%, a pattern mainly related to shifts in pH. AM fungal abundance and diversity, however, did not differ despite clearly increased soil fertility in AfDE, with 3.7 and 1.7 times greater extractable P and total N content, respectively. The absence of detrimental effects on AM fungi, often seen following applications of inorganic fertilizers, and the enhanced role of saprobic fungi relevant for mineralization and C sequestration support previous assertions of this management type as a sustainable alternative agricultural practice.